New reptile shows dinosaurs and pterosaurs evolved among diverse precursors - Müller, Rodrigo T.; Ezcurra, Martín D.; Garcia, Mauricio S.; Agnolín, Federico L.; Stocker, Michelle R.; Novas, Fernando E.; Soares, Marina B.; Kellner, Alexander W. A.; Nesbitt, Sterling J. (Nature (London), 2023)
Dinosaurs and pterosaurs have remarkable diversity and disparity through most of the Mesozoic Era 1 – 3 . Soon after their origins, these reptiles diversified into a number of long-lived lineages, evolved unprecedented ecologies (for example, flying, large herbivorous forms) and spread across Pangaea 4 , 5 . Recent discoveries of dinosaur and pterosaur precursors 6 – 10 demonstrated that these animals were also speciose and widespread, but those precursors have few if any well-preserved skulls, hands and associated skeletons 11 , 12 . Here we present a well-preserved partial skeleton (Upper Triassic, Brazil) of the new lagerpetid Venetoraptor gassenae gen. et sp. nov. that offers a more comprehensive look into the skull and ecology of one of these precursors. Its skull has a sharp, raptorial-like beak, preceding that of dinosaurs by around 80 million years, and a large hand with long, trenchant claws that firmly establishes the loss of obligatory quadrupedalism in these precursor lineages. Combining anatomical information of the new species with other dinosaur and pterosaur precursors shows that morphological disparity of precursors resembles that of Triassic pterosaurs and exceeds that of Triassic dinosaurs. Thus, the ‘success’ of pterosaurs and dinosaurs was a result of differential survival among a broader pool of ecomorphological variation. Our results show that the morphological diversity of ornithodirans started to flourish among early-diverging lineages and not only after the origins of dinosaurs and pterosaurs. A well-preserved partial skeleton (Upper Triassic, Brazil) of the new lagerpetid Venetoraptor gassenae gen. et sp. nov. offers a more comprehensive look into the skull and ecology of dinosaur and pterosaur precursors.